Weighted composition operators on weighted Bergman spaces induced by doubling weights - Du, Juntao; Li, Songxiao; Shi, Yecheng (MATHEMATICA SCANDINAVICA, 2020)
In this paper, we investigate the boundedness, compactness, essential norm and the Schatten class of weighted composition operators uC_φ on Bergman type spaces A_ω ^p induced by a doubling weight ω. Let X={uH(D ): uC_φ A_ω ^p→ A_ω ^p is bounded}. For some regular weights ω, we obtain that X=H^∞ if and only if ϕ is a finite Blaschke product.